2004
DOI: 10.1892/0891-6640(2004)18<728:pooaih>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Once-Daily Amikacin in Healthy Foals and Therapeutic Drug Monitoring in Hospitalized Equine Neonates

Abstract: The objectives of this study were to investigate the pharmacokinetics of once-daily amikacin in healthy neonates, to determine amikacin concentrations in hospitalized foals, and to determine the minimum inhibitory concentrations (MICs) of amikacin against gram-negative isolates from blood cultures in septic foals. Median half-life, clearance, and volume of distribution of amikacin in healthy 2-to 3-day-old foals after administration of an intravenous bolus of amikacin (25 mg/kg) were 5.07 hours (4.86-5.45 hour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…Subsequently, a higher peak concentration of amikacin as observed in the middle carpal joint may result in a prolonged PAE and potentially a longer duration of action. The median concentration of amikacin in the middle carpal and metacarpophalangeal joints at 24 hours were still above the MIC of the Gram‐negative isolates from equine neonates (4 μg/mL) …”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Subsequently, a higher peak concentration of amikacin as observed in the middle carpal joint may result in a prolonged PAE and potentially a longer duration of action. The median concentration of amikacin in the middle carpal and metacarpophalangeal joints at 24 hours were still above the MIC of the Gram‐negative isolates from equine neonates (4 μg/mL) …”
Section: Discussionmentioning
confidence: 87%
“…Caron et al published on the MIC of methicillin resistant S. aureus isolates from horses where the MIC varied from 2 to 32 μg/mL. Another study reported that all Gram‐negative bacterial isolates from equine neonates had an MIC 90 of 4 μg/mL. Orsini et al measured just 6 isolates that had MIC that varied from 0.5 to 128 μg/mL, and finally Erol et al reported that nocardioform actinomycetes had an MIC 90 of 32 μg/mL.…”
Section: Discussionmentioning
confidence: 99%
“…The high Cl in foals, compared with adults, was an unexpected finding. Usually Cl is reduced in neonates and increases with age, 20–24 but allometry also may be a factor causing a higher Cl owing to lower body weight. Allometric scaling shows that, for some drugs, Cl increases inversely with body weight 25 …”
Section: Discussionmentioning
confidence: 99%
“…This technique has been previously validated in plasma [11] and synovial fluid of horses [12], and several studies have used the same methodology for the measurement of amikacin in blood and synovial fluid [13,14]. Samples were centrifuged at 1700 g for 5 min, the supernatant stored in plastic tubes and frozen at À78°C until analysis.…”
Section: Measurement Of Amikacin Sulfate Concentrationsmentioning
confidence: 99%